Megasura Point of Sales and Financial Management System - Hamdan, Mohamed Hazizi; ZAINAL, Dr. NUREZAYANA (Applied Information Technology And Computer Science, 2025)
The Megasura Enterprise is a franchised store of Lesong Mart that is based on muslin and halal products. The financial and point of sales management system aims to replace an existing client-based system with a web-based system which is more accessible and aims to remove any use of physical data stores for financial management that includes calculating the amount of profit and sales, calculating the tax payment and manage inventory with invoicing. The system also aims to provide a smooth operation for the staff of Megasura Enterprise that removes any loading time to ensure high customer satisfaction during each purchase transaction. The goal of this project would be to design and develop a financial and point of sales management system using an object-oriented approach on a web application as well as to test the developed system using alpha, beta, performance testing, and user acceptance tests. The system is developed in PHP programming language and the data is stored on a MySQL database that is hosted on a web service. From this application, it is expected that the staff to have a better user experience compared to the previous system and indirectly improve the store customer’s experience.